Metrical counterpoint and semanticization of form in a poem by Fernando Pessoa - Brito, Paulo Henriques (2014)
Relying on the notion of metrical counterpoint developed in an earlier article, the author demonstrates the existence of a dense metrical structure in Fernando Pessoa’s poem “Pierrot bêbado” which may be analyzed as consisting of two levels in a relationship of counterpoint. It is also shown that the metrical counterpoint interacts with the semantic level, in that the character of Pierrot mentioned in the title appears in the body of the poem mostly as an inversion in the counterpointed meters.